Supervision, Discipline and Work Stress on Employee Performance at PT. Jaya Mandiri Building Medan - Fredie; Willkent; Rahmat Alamsyah Harahap (Jurnal Mantik, 2021)
This study aims to determine the effect of supervision, discipline and work stress on employee performance. This type of research is explanatory research. The entire population is 147 employees. Due to a large population, the sampling technique will be reduced by using the Slovin formula with an error tolerance level of 5% so that there are as many as 108 respondents in the study which will be distributed with questionnaires measured by a Likert scale. The data analysis used multiple linear regression analysis, and the coefficient of determination as well as simultaneous test, and partial test. The results showed that supervision, discipline and work stress partially, andsimultaneously have a positive, and significant effect on employee performance. Based on the results of this study, the implications for management are to further improve the better supervision, discipline and work stress.